The University of the Philippines Science Education Center a descriptive study - Sirinam, Wasun 1945- (s.n.], 1972)
The need for the establishment of the U.P.-S.E.C. was described in this paper. It analyzed how it contributes to the improvement of science education in the country through its objectives, organizations, programs, and projects.